2012
DOI: 10.1021/es302285h
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Recovery of Benthic Communities in Sediments Amended with Activated Carbon

Abstract: Using activated carbon (AC) for sediment remediation may have negative effects on benthic communities. To date, most AC effect studies were short-term and limited to single species laboratory tests. Here, we studied the effects of AC on the recolonization of benthic communities. Sediment from an unpolluted site was amended with increasing levels of AC, placed in trays and randomly embedded in the original site, which acted as a donor system for recolonization of benthic species. After 3 and 15 months, the tray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 39 publications
(101 reference statements)
5
70
2
2
Order By: Relevance
“…For example, the larger AC particles (100–200 μm) and relative organic carbon-rich river sediment (TOC 4–6%) may explain the limited negative effects to a fresh water community in Grasse River (Beckingham et al 2013). Moreover, the mild initial effects and full recovery of the benthic community 1 year after exposure to powdered AC in an un-contaminated fresh water experimental ditch may also be attributed to less stress due to organic carbon rich (TOC 8%) sediment (Kupryianchyk et al 2012). Hence, the negative response of the benthic community by powdered AC at 30 m depth in the present study may have been determined by a multitude of variables, e.g., poor available organic carbon (TOC only 1.1–1.6%), in concert with organic carbon binding by AC, reduced biodeposition, and physiologically negative effects by the fine, and possibly sharp, AC particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the larger AC particles (100–200 μm) and relative organic carbon-rich river sediment (TOC 4–6%) may explain the limited negative effects to a fresh water community in Grasse River (Beckingham et al 2013). Moreover, the mild initial effects and full recovery of the benthic community 1 year after exposure to powdered AC in an un-contaminated fresh water experimental ditch may also be attributed to less stress due to organic carbon rich (TOC 8%) sediment (Kupryianchyk et al 2012). Hence, the negative response of the benthic community by powdered AC at 30 m depth in the present study may have been determined by a multitude of variables, e.g., poor available organic carbon (TOC only 1.1–1.6%), in concert with organic carbon binding by AC, reduced biodeposition, and physiologically negative effects by the fine, and possibly sharp, AC particles.…”
Section: Discussionmentioning
confidence: 99%
“…No negative effects were shown with granular AC in a fresh water benthic community in Grasse River, USA (Beckingham et al 2013). A benthic community in a fresh water ditch (Veenkampen, The Netherlands) showed an initial perturbation followed by recolonization and recovery 1 year after exposure of fine particle AC (Kupryianchyk et al 2012). In contrast, a marine benthic community showed a significant decrease in both the number of species and in their respective abundances 1 year after capping in situ with powdered AC in the Trondheim Harbor, Norway (Cornelissen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review by Janssen and Beckingham () found that impacts to benthic organisms resulting from AC exposure were observed in one‐fifth of 82 tests (primarily laboratory studies). Importantly, community effects have been observed more rarely in AC field pilot demonstrations compared to laboratory tests and often diminish within 1 or 2 years following placement (Cornelissen et al ; Kupryianchyk et al ), particularly in depositional environments where new (typically cleaner) sediment continues to deposit over time.…”
Section: Potential Negative Ecological Impactsmentioning
confidence: 99%
“…10,12−14 Other studies report no influence of AC on organism growth or lipid contents, and some observed an increase of survival when exposure to pollutants was reduced by AC addition. 11,15,16 Most of the previous studies were designed to assess contaminant bioaccumulation rather than an organism's health during exposure. While AC amendment reduces the availability of HOCs to benthic organisms, other organic molecules, including dissolved organic carbon, and nutrients may become less available as well.…”
Section: ■ Introductionmentioning
confidence: 99%